Strategi Pengembangan Agribisnis Beras Merah Organik di Subak Wongayabetan, Desa Mengesta, Kecamatan Penebel, Kabupaten Tabanan - Luh Anggreni Dewi; Agung Ayu Ambarawati; Wayan Budiasa (Universitas Udayana, 2016)
Bali tourism development together with consumer awareness on health is an opportunity for organic products producers. In order to take this opportunity, Subak Wongayabetan needs a strategy to develop agribusiness development of organic brown rice. The objective of this research is to investigate alternative strategies and priorities to the strategies run by the Subak Wongayabetan in managing organic brown rice agribusiness development. Respondents in this research were selected purposively regarding their expertise and knowledge of the research. Primary data were collected by conducting focus group discussions, surveys, and in-depth interviews. Secondary data were collected from publications. Formulation of alternative and priority strategies was using SWOT analysis and QSPM. The results show that alternative strategies of agribusiness development for organic brown rice include: 1) increasing productivity of organic brown rice, 2) improving the skills of processing organic fertilizers and pesticides, 3) developing subak as agrotourism, 4) cooperate with Village Unit Enterprises , 5) expansion of wetland organic field, 6) training of farming book-keeping , 7) intensifying the use of packaging and branding, 8) labor recruitment from outside the region, 9) intensifying integrated pest and disease , 10) socialization of organic products to consumers, 11) intensification of Internal Control System (ICS), and 12) database improvement and Management Information System to support the sustainability of organic certification. The most priority strategy in this research shows that ICS intensification is selected.. In supporting the development of agribusiness organic brown rice, members of Subak Wongayabetan are suggested to do book-keeping of their farming costs and returns, more intensive socialization to the benefits of organic farming, and creating more innovative actions through packaging and branding use to increase the products value.